Parental Responsibility Toward Child as Criminal Offender in Indonesian Criminal Reform - Jananuraga, Hatma Aditya; Cahyaningtyas, Irma (IJCLS (Indonesian Journal of Criminal Law Studies), 2021)
Parents as the first guardian of the child make their role irreplaceable for children. The negligence of parents in interpreting their role as caretakers of children can have an impact on children's development. True children do not have the ability to plan a crime. ABH is more accurately seen as a victim. This study reveals the responsibility of parents to child offenders of criminal offenses in Indonesian law today and its reforms in the future. This study uses a qualitative approach and normative juridical research methods. Code No. 11 of 2012 concerning the Juvenile Criminal Justice System implies the use of Restorative Justice in every settlement of juvenile crime. There is no formal legality of parents' responsibility for criminal acts committed by children, however, the Law on the Criminal Justice System for Children only regulates the responsibility of parents in the form of compensation in terms of diversion. The principle of Vicarious Liability can be applied to child crimes in the future. The principle of Vicarious Liability can be clearly stated in the regulations relating to juvenile punishment. The principle of vicarious liability can be applied to parents for criminal acts committed by children in the context of the transfer of criminal acts, based on legal objectives, namely justice, certainty and legal usefulness in the application of criminal law in Indonesia.